Working : Red Dot Design Yearbook 2016/2017 - Zec, Peter, 1956- (Essen : Red Dot, 2016)
"Working" presents products from work and technology oriented fields such as offices, heating and air conditioning, industry and crafts, life science and medicine, as well as computers and information technology. Additionally, the design team of the year, as well as designer and jury portraits will be shown.